VARIATIONAL MUTI-STEPS METHOD TO SOLVE DAMPED OSCILLATION EQUATION - Adam, Riza Ibnu; Susilawati, Susilawati; Rizal, Adhi (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2017)
This paper aims to identifying the numerical method accuracy of the analytical solution of the damped oscillation equation motion. Adams method ofÂ 4th order, Milne method and Adams-Simpson method are used to find numerical solutions. Value of y(1), y(2), y(3) obtained from The 4th order Runge-Kutta method. They used as initial value of multistep method. Then, the numerical solution result was compared with analytical solution. From the research result, it is found that 4th order Adams method has the best accuracy.